The Impact Of Bullying On Children In The School Environment Communication Psychology Perspective - Moch Nurcholis Majid; Opam Pahmi Sopandi (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2023)
Bullying, or in Bahasa Indonesia referred to as bullying, is any act of physical or non-physical oppression or violence carried out intentionally or unintentionally by one person or those who feel they are stronger and have the power to hurt on an ongoing basis. There have been many cases of bullying in Indonesia, especially in schools or educational institutions. Usually bullying cases occur due to differences in body size, physique, communication skills, gender and social status. And there is an imbalance of physical strength and power that is misused to disturb and isolate the victim. In this study, researchers interviewed around 21 students who had experienced bullying, and also 3 BP / BK teachers who were representatives of the school. Some of these respondents aim to strengthen this research. The method of this research paper is qualitative research, using observation and interviews that contain information because it is more objective, detailed, and can be processed to get some conclusions from an experiment. This research contains several examples of bullying cases that occur in schools, the form of bullying itself, the psychological impact of communication that occurs on students, and provides solutions as a preventive measure so that bullying cases do not continue to occur.